First lessons learnt from the Mediterranean ERA-WIDE projects_x001B_ - Pancera A.; Papageorgiou K.; Boutros S.; Bousselmi L.; Abdelhak S.; Al-Bawab A. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
In 2010, the European Commission launched a new scheme targeting directly research centres from the European Neighbourhood Policy (ENP) countries. The ERA-WIDE scheme was aimed at reinforcing the cooperation capacities of the ENP countries, involving the different thematic priorities of FP7. Between 2010 and 2011, approximately thirty ERA-WIDE projects were selected for funding with the focus being on the Mediterranean Partner Countries. This paper presents a preliminary assessment of these projects, highlighting the lessons learnt so far. It is divided into four main parts. The first part presents the ERAWIDE scheme and its potential impact in terms of human capital development. Part two gives an overview of the ERA-WIDE projects funded across the Southern Mediterranean region. Part three highlights some experimental practices used to coordinate the projects at a regional level. It examines the extent to which these practices can contribute to strengthening the impacts of the projects and complementing previous initiatives funded by the International Cooperation Programme of DG Research and Innovation under FP7. The last part of the paper presents some indicators employed to assess the final impact expected at a later stage, as well as some recommendations to make the most of this approach. This paper employs material and observations acquired by the authors through their involvement in ERA-WIDE INCO activities as project officers, coordinators and reviewers.